Off Time Independently Affects Quality of Life in Advanced Parkinson's Disease (APD) Patients but Not in Non-APD Patients: Results from the Self-Reported Japanese Quality-of-Life Survey of Parkinson's Disease (JAQPAD) Study. (12th October 2021) - Hayashi, Yuka; Nakagawa, Ryoko; Ishido, Miwako; Yoshinaga, Yoko; Watanabe, Jun; Kurihara, Kanako; Nagaki, Koichi; Ogura, Hiromu; Mishima, Takayasu; Fujioka, Shinsuke; Tsuboi, Yoshio
Abstract : Introduction . Parkinson's disease (PD) is characterized by a triad of motor symptoms and several nonmotor symptoms (NMS). Identifying the most appropriate treatment is essential for improving patient quality of life (QoL). However, it is still not known which PD symptoms more commonly affect patients with advanced PD (APD) versus non-APD. This study examined the factors that most affected the QoL of patients with APD (defined using the 5-2-1 criteria: ≥5 oral levodopa doses a day, off time ≥2 hours a day, or troublesome dyskinesia ≥1 hour a day) versus non-APD in a large Japanese population using the Japanese Quality-of-Life Survey of Parkinson's Disease (JAQPAD) study. Methods . Participants in this self-reported survey-based study included all members of the Japan Parkinson's Disease Association. Questionnaires assessing NMS and QoL (e.g., the 8-item PD Questionnaire [PDQ-8]) were included. Univariate and multivariate regression analyses were conducted to identify clinical factors impacting QoL using the PDQ-8 Summary Index (PDQ-8 SI). Results . Of the 3022 eligible patients, 864 were classified as having non-APD and 1599 as having APD. QoL as assessed by the PDQ-8 SI was notably worse in patients with APD versus non-APD (39.2 vs. 26.9, p < 0.0001 ). Although off time affected QoL only in patients with APD, PD duration and the NMS Questionnaire score significantly contributed to the QoL in both patients with APD and non-APD. Conclusions . This study identified the factors more commonly associated with worse QoL in patients with APD versus non-APD. Our findings offer new insights for providing optimal treatment and improving treatment satisfaction in patients with PD.